Strategies for the Transformation of Traditional Islamic Boarding Schools in Aceh Singkil: Integrating Education, Social, and Religious Aspects - Suryati Suryati; Eka Sri Mulyani; Sehat Ihsan Shadiqin (Tafkir: Interdisciplinary Journal of Islamic Education, 2026)
The transformation of traditional Islamic boarding schools (pesantren) in peripheral areas such as Aceh Singkil reflects an adaptive response to the demands of Islamic education modernization, social challenges, and the need to integrate Islamic values within contemporary society. Pesantren are no longer merely centers for classical religious transmission; they have evolved into dynamic institutions capable of educational, social, and religious innovation. This study explores the transformation strategies implemented by three prominent pesantren in Aceh Singkil Dayah Babussalam, Darul Muta’alimin, and Darul Hasanah focusing on the integration of educational, social, and religious dimensions. This research employed a qualitative case study approach with data collected through in-depth interviews, participatory observation, and documentation. The analytical framework used was Talcott Parsons' AGIL model (Adaptation, Goal Attainment, Integration, Latency). The findings reveal that each pesantren pursued distinct innovations: curriculum integration, digital learning initiatives, alumni involvement in institutional reform, and the promotion of Islamic moderation through leadership and community outreach. These institutions have successfully built integrative models rooted in traditional values while remaining responsive to contemporary demands. The transformation observed is evolutionary, collaborative, and centrally led by kyai figures who serve both as preservers of tradition and agents of change. This study contributes to the discourse on adaptive Islamic education models that retain salafiyah authenticity while meeting global educational challenges.